Participación de los padres de familias y su influencia en el rendimiento académico de los estudiantes de segundo año de la escuela de Educación Básica Juan E. Verdesoto de la ciudad de Babahoyo - Zapata Calderón, Freddy Gualberto (2020)
This research project is executed by observing the problem of low academic performance due to the lack of active participation of parents in the School of Basic Education "JUAN E. VERDESOTO", which allowed determining the intrinsic factors of the problem. Its theoretical framework is based on the main ideas of important international exponents in pedagogical, psychological and scientific matters on this research, whose general objective of the project is to examine the influence of the level of organization through a theoretical and structural theoretical study to achieve the active participation of parents. Through this problem, the present proposal identified as: PARTICIPATION OF THE PARENTS OF FAMILIES AND THEIR INFLUENCE IN THE ACADEMIC PERFORMANCE OF SECOND YEAR STUDENTS OF THE JUAN E. VERDESOTO BASIC EDUCATION SCHOOL OF THE CITY OF BABAHOYO. The application of methodological training seeks to adapt those involved to the reality that they have educational needs, we intend to eliminate the barriers that limit learning in one way or another in the education system, thereby achieving equality and equitable opportunities.